Peningkatan Efisiensi Operasional dan Strategi Manajemen Persediaan pada Fried Chiken Dua Soedara di Cikarang Baru - Fathurohman Fathurohman; Tri Mulyani Kartini; Nasrun Baldah; Etty Zuliawati Zed; Suwara Suwara (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The Dua Soedara Fried Chicken MSME in Cikarang Baru faces operational inefficiencies, particularly a high daily waste rate of 3 pieces, or 3%, due to non-data-driven production planning. As independently managed micro-enterprises (solopreneurs), partners lack formal Standard Operating Procedures (SOPs) and digital financial recording systems, leading to a high risk of quality inconsistencies and cash flow uncertainty. This community service initiative aims to improve operational efficiency and strengthen inventory management strategies through digitization and standardization of business processes. The implementation method used is a participatory mentoring approach (Action-Reflection), which includes socialization, demand forecasting training, the application of digital marketing technology, and evaluation assistance. The primary focus of this initiative is the transformation of traditional management to data-driven management to minimize waste. The implemented solutions include the development of standard production SOP documents and the implementation of daily production control tables using the Moving Average method based on historical sales data. Furthermore, branding optimization was carried out through Google Business Profile registration to increase local visibility and training in a simple financial recording application. The results of this activity demonstrated a significant increase in operational efficiency, marked by a decrease in product waste from 3 pieces to less than 1 piece per day (>60% efficiency). Furthermore, marketing digitalization successfully expanded partners' market reach beyond their physical stores. Overall, this program provides a foundation for partners to run their businesses in a more scalable, professional, and sustainable manner.